Analisis Kelayakan Nasabah Pembiayaan Qardhul Hasan di Koperasi Syariah Baituttamkin Lombok Barat - Wahidayani Wahidayani; Siti Ahdina Saadatirrohmi (Universitas Islam Negeri Mataram, 2022)
This study aims to describe the feasibility analysis of customers receiving qardhul hasan financing during the covid-19 pandemic and the obstacles faced in assessing the feasibility of customers at the Baituttamkin Sharia Cooperative Kediri Unit. The type of research used in this research is descriptive research with a qualitative approach. In the method of data collection using the method of observation, interviews and documentation. The data analysis technique used is data reduction, data display and conclusion drawing, while for the validity of the data using the credibility test, transferability test, dependability test, confirmability test. The results of the study prove that the feasibility analysis of customers in the Baituttamkin Islamic cooperative unit Kediri does not all apply the 5C and 7P principles but rather prioritizes the character side. Good character will affect all sides of the 5C or 7P principles by prioritizing the assessment of the character aspect is a very appropriate step because character will affect everything that is in a person. Good character, making other aspects such as capacity, capital, collateral, and condition of the customer's economy will have a positive impact from that character.